Networks and graphs : techniques and computational methods - Smith, David K. (David Kendall), 1950- (Horwood Pub., 2003)
Dr Smith here presents essential mathematical and computational ideas of network optimisation for senior undergraduate and postgraduate students in mathematics, computer science and operational research. He shows how algorithms can be used for finding optimal paths and flows, identifying trees in networks, and optimal matching. Later chapters discuss postman and salesperson tours, and demonstrate how many network problems are related to the ''minimal-cost feasible-flow'' problem. Techniques are presented both informally and with mathematical rigour and aspects of computation, especially of complexity, have been included. Numerous examples and diagrams illustrate the techniques and applications. The book also includes problem exercises with tutorial hints. Presents essential mathematical and computational ideas of network optimisation for senior undergraduate and postgraduate students in mathematics, computer science and operational researchDemonstrates how algorithms can be used for finding optimal paths and flows, identifying trees in networks and optimal matchingNumerous examples and diagrams illustrate the techniques and applications.